EVALUASI KONDISI KUALITAS AIR BERDASARKAN DAMPAK BEBAN PENCEMARAN TERHADAP SEBARAN OKSIGEN TERLARUT DI SUNGAI GUNUNG PASANG KABUPATEN JEMBER - Elida Novita; Bawon Rani Yudhika Anwar; Hendra Andiananta Pradana (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2021)
Gunung Pasang River is as raw water supply for the human activity. However, it is utilized as waste disposal from community activities, agro-tourism, and rubber factories. These activities have the potential to reduce water river quality. The efforts to river pollution prevention that can be taken are to examine for capacity of the rivers to reduce pollutant naturally. The research focused to analysis the pollution load, oxygen dissolved distribution (deoxygenation and reoxygenation rate), and the total pollution load of the Gunung Pasang river utilized the Streeter-Phelps formula. The study was conducted in November – December in 2019 at the Gunung Pasang River with a river length of 300 m which was divided into 3 segments with 4 monitoring points (GP01, GP02, GP03, GP04). Analysis of the parameters i.e. DO and BOD to measure the water quality degradation in the river and the resulting graph of oxygen reduction. The method refers to Minister of the Environment Decree no. 110/2003.The results showed that the average pollution load value was 6.32 kg/day. The range of deoxygenation and reoxygenation rates is 2.67 - 5.36 mg/L.day and 32.77 - 64.71 mg/L.day respectively. The Reoxygenation rate was greater than deoxygenation. This phenomenon reflected that the Gunung Pasang River has a good self – purification performance. The average pollution load capacity of the river is 2.17 kg/day.Keywords: total pollution capacity; oxygen distribution; self – purification; water quality monitoring.